1975
DOI: 10.1212/wnl.25.5.477
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular anoxia‐ischemia lesions in the human brain

Abstract: The clinical and pathologic data are presented on three patients who had clinical anoxia-ischemia in combination with serum hyperosmolality. The pathologic lesions consisted of perivascular necrosis, predominantly involving small vessels in the cerebral cortex. No intraluminal thromboembolic material was found in any of the vessels. The lesions are reminiscent of "no-reflow" lesions seen in experimental animals rendered ischemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although the neuronal loss could be induced by recurrent hypoxic-ischemic episodes owing to respiratory depression during the intoxicated state, the reduction of GFAP-positive astrocytes argues against such a phenomenon as the sole cause. Furthermore, CNS lesions after global hypoxic-ischemic damage are predominantly seen in the Purkinje cell layer of the cerebellum and the hippocampal formation (13). Because the nerve cell density in these regions was not significantly changed between both groups, other factors must be of pathogenetic significance.…”
Section: Discussionmentioning
confidence: 98%
“…Although the neuronal loss could be induced by recurrent hypoxic-ischemic episodes owing to respiratory depression during the intoxicated state, the reduction of GFAP-positive astrocytes argues against such a phenomenon as the sole cause. Furthermore, CNS lesions after global hypoxic-ischemic damage are predominantly seen in the Purkinje cell layer of the cerebellum and the hippocampal formation (13). Because the nerve cell density in these regions was not significantly changed between both groups, other factors must be of pathogenetic significance.…”
Section: Discussionmentioning
confidence: 98%
“…Second, the perivascular lesions seen in humans following circulatory arrest combined with hyperosmolality are predominantly situated around penetrating cortical vessels and not associated with capillaries. 8 The further possibility that larger vessel occlusion might be caused by spasm is suggested by Wade and associates 13 who have demonstrated increased concentrations of potassium in rat brain interstitial fluid following ischemia and have postulated that the no-reflow state which they observed might possibly be due to vascular contraction since it is known that high potassium concentrations can cause contractions of vascular smooth muscle. 14 Zervas et a/.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have observed perivascular patterns of necrosis in human cerebral cortices following ischemia combined with serum hyperosmolality. 8 Upon reexamination of that material we concluded that the focal ischemic areas were associated with penetrating vessels large enough to contain significant amounts of smooth muscle in their walls. This observation raised the question of whether spasm of intraparenchymal cerebral vessels could occur and if it could be contributory to post-ischemic no-reflow in the cerebral cortex.…”
Section: S U M M a R Y The Reaction Of Brain Parenchymal Vessels In Amentioning
confidence: 97%